A computer-based systematic survey reveals the predominance of small inverted-repeat elements in wild-type rice genes. - Bureau, T E (1996)
Several recent reports indicate that mobile elements are frequently found in and flanking many wild-type plant genes. To determine the extent of this association, we performed computer-based systematic searches to identify mobile elements in the genes of two "model" plants, Oryza sativa (domesticated rice) and Arabidopsis thaliana. Whereas 32 common sequences belonging to nine putative mobile element families were found in the noncoding regions of rice genes, none were found in Arabidopsis genes. Five of the nine families (Gaijin, Castaway, Ditto, Wanderer, and Explorer) are first described in this report, while the other four were described previously (Tourist, Stowaway, p-SINE1, and Amy/LTP). Sequence similarity, structural similarity, and documentation of past mobility strongly suggests that many of the rice common sequences are bona fide mobile elements. Members of four of the new rice mobile element families are similar in some respects to members of the previously identified inverted-repeat element families, Tourist and Stowaway. Together these elements are the most prevalent type of transposons found in the rice genes surveyed and form a unique collection of inverted-repeat transposons we refer to as miniature inverted-repeat transposable elements or MITEs. The sequence and structure of MITEs are clearly distinct from short or long interspersed nuclear elements (SINEs or LINEs), the most common transposable elements associated with mammalian nuclear genes. Mobile elements, therefore, are associated with both animal and plant genes, but the identity of these elements is strikingly different.